Influence of creep feeding on individual consumption characteristics and growth performance of neonatal and weanling pigs - Sulabo, Rommel Casilda (Kansas State University, 2009)
Five experiments were performed to determine the influence of creep feeding on individual consumption characteristics and growth performance of neonatal and weanling pigs. These evaluated the effects of lactation feed intake and creep feeding (n = 84 litters; Exp. 1), creep feeding duration (n = 54 litters; Exp. 2), creep feeder design and feed accessibility (n = 54 litters; Exp. 3), organoleptic properties of the creep feed (n = 50 litters; Exp. 4) and creep diet complexity (n = 96 litters; Exp. 5). In summary, creep feeding did not affect preweaning gains and weaning weights of pigs weaned at 3 weeks of age. Creep feeding for 18 d did not influence sow performance. However, creep feeding tended to improve litter weaning weights due to improved survivability. Creep feed consumption was related to piglet maturity rather than the induction of creep feeding. In both experimental and field conditions, pigs that consumed creep feed (eaters) had greater post-weaning feed intake and daily gains compared to non-eaters (pigs that did not consume creep feed) and non-creep fed pigs. This led to improvements in pig weight uniformity and reduction of the severity of post-weaning lag. These benefits were achieved regardless of weaning weight, the complexity of the creep diet, and the duration of creep feeding. The proportion of eaters of creep feed in whole litters can be manipulated. Longer duration of creep feeding increased the proportion of eaters. A rotary creep feeder with a hopper created the most eaters with the lowest creep feed disappearance. Creep diet complexity had the greatest effect in increasing the proportion of pigs consuming creep feed. On the other hand, low feed intake of lactating sows and adding feed flavors to the creep feed did not affect creep feed consumption and the proportion of pigs consuming creep feed. Therefore, creep feeding that focuses in encouraging more suckling piglets to eat is beneficial in producing weanling pigs that are better adapted to weaning, which improves post-weaning performance.
Keywords: Creep feeding; Neonatal pigs; Growth; Creep feeding duration; Creep feeder design; Creep diet complexity; Agriculture, Animal Culture and Nutrition (0475)